Characterization of rhizosphere bacterial community and berry quality of Hutai No.8 (Vitis vinifera L.) with different ages, and their relations. (19th April 2019) - Ji, Wei; Han, Kai; Cai, Yinghui; Mu, Yuanyuan; Zhao, Liang; Zhang, Min; Hou, Chao; Gao, Meiying; Zhao, Qifeng
Abstract: BACKGROUND: Rhizosphere soil microbial communities play an important role in grapevine growth. However, the relationship of the rhizosphere soil bacterial community and berry quality of Hutai No.8 grape with different tree‐ages is unclear. In this work, the Biolog‐ECO technique was used to explore the functional diversity of the rhizosphere soil bacterial communities of Hutai No.8 grape with five ages (3, 5, 7, 9 and 11 years old). Meanwhile, grape berry quality indicators related to berry appearance, flavor and functional substance quality was also examined. RESULTS: Principal component analysis of grape berry quality mainly separated 3‐year‐old (first bear fruit) and the other tree‐ages. In particular, peel weight and total soluble solid content of 3‐year‐old grape berry was significantly less than that of others. Furthermore, average well color development, species richness and Shannon's diversity index increased significantly with grapevine age. Moreover, the metabolic activities and functional diversity of soil microbial communities in using carbon sources were significantly increasing with grapevine age. Moreover, there were significant correlation between physicochemical indices of grape berry quality and six functional categories of carbon sources. CONCLUSION: Tree‐ages could greatly affect the rhizosphere microbial community structure and richness, and then affect the grape berry quality. © 2019 Society of Chemical Industry